Standardizing the reporting of percutaneous nephrolithotomy complications - Philippe D Violette; John D Denstedt (Indian Journal of Urology, 2014)
Accurate reporting of complications is an essential component to critical appraisal and innovation in surgery and specifically with percutaneous nephrolithotomy (PCNL). We review the evolution of complication reporting for PCNL and suggest future directions for innovation. A selective review was carried out using Pubmed. Key search terms and their combinations included percutaneous, anatrophic, nephrolithotomy, PCNL, complications, Clavien, Martin score, bleeding, bowel injury, perforation, fever, sepsis. The references from relevant papers and reviews as well as AUA and EAU guidelines were also scanned for inclusion. PCNL has become the procedure of choice for large renal stones owing to decreased morbidity over alternative procedures. Both common and rare complications have been described in large case series, small randomized controlled trials, and case reports in an unstandardized form. Although these reports have provided an informative starting point, a standardized complication reporting methodology is necessary to enable appropriate comparisons between institutions, time periods, or innovations in technique. The Clavien-Dindo grading system has become widely accepted in urology and has facilitated the study of PCNL complications. Future research should focus on adaptions of this system to render it more comprehensive and applicable to PCNL.